The Symbiosome: Legume and Rhizobia Co-evolution toward a Nitrogen-Fixing Organelle? - Coba de la Peña, Teodoro; Fedorova, Elena; Pueyo, José J.; Lucas, M. Mercedes (Frontiers in Plant Science, 2018)
In legume nodules, symbiosomes enclosing endosymbiotic rhizobial bacteria act like plant organelles in terms of nitrogen fixation, as they develop a mutual metabolic dependence with the host legume. In most legumes, rhizobia infect post-mitotic cells, which lose their ability to divide. Nevertheless, certain nodules maintain their capacity to undergo mitosis after infection. Here, we review the existing knowledge on legume symbiosomes from an evolutionary and developmental perspective in the context of the different interactions between diazotrophic bacteria and eukaryotes. It is concluded that the symbiosome possesses organelle-like characteristics due to its metabolic behavior, the composite origin and differentiation of its membrane, the retargeting of host cell’s proteins, the control of microsymbiont proliferation and differentiation by the host legume, and the cytoskeleton dynamics and symbiosome segregation during division of rhizobia-infected cells. The existing knowledge on symbiosome features suggests that it might be considered a nitrogen-fixing link in organelle evolution, and that different legume symbiosomes could represent some different stages in an evolutionary process towards a nitrogen-fixing organelle. Different degrees of symbiosome evolution can be defined, which are related to the various ways of rhizobial infection and to the different nodule types.